Glycemic impact of intensified self monitoring of blood glucose in insulin treated subjects with type 2 diabetes mellitus - Ugwu, Ejiofor T.; Gezawa, Ibrahim D.; Adeleye, Olufunmilayo O. (Journal of Social Health and Diabetes, 2018)
Objective:The aim of this study was to evaluate if intensified self-monitoring of blood glucose (SMBG) improves glycemic control in insulin-treated subjects with type 2 diabetes mellitus (T2DM).Methods:Ninety-six adults with stable but poorly controlled [glycated hemoglobin (HbA1c) level >7.5%] T2DM receiving twice-daily biphasic insulin were randomly assigned to either of the two groups: intensive monitors (IM) that performed SMBG at least twice daily or conventional monitors (CM) that performed SMBG at their discretionary frequency for 12 weeks. Demographic, clinical, and glycemic indices, including fasting blood glucose (FBG), postprandial glucose (PPG), and HbA1c, were compared at baseline and week 12.Results:A total of 71 subjects (25 IM and 46 CM) completed the study. Both groups had similar HbA1c at baseline. From baseline to week 12, the IM group had higher mean daily test strip usage (P <0.001), engaged in more frequent insulin dose adjustments (P <0.001), and attained greater daily insulin dosage (P = 0.002). All glycemic indices including FBG, PPG, and HbA1c improved significantly from baseline to week 12 in the IM but not in the CM group. HbA1c level declined by −1.2 ±0.4% in the IM group (P = 0.002). There was no difference in the frequency of hypoglycemia in both groups. The monthly cost of intensified SMBG was nearly four times that of conventional monitoring (P <0.001).Conclusion:Both short- and long-term glycemic control significantly improved by intensified SMBG in stable but poorly controlled insulin-treated adults with T2DM. Intensified SMBG enabled better self-titration of insulin and probably other self-care practices. This benefit, however, occurred at the expense of costs that may be difficult to sustain in resource-poor countries.
Keywords: Blood glucose; insulin; Nigeria; self-monitoring; type 2 diabetes mellitus